Stylopauropus plicatus Scheller, 2011, n. sp. - Scheller, Ulf (Zenodo, 2011)
Stylopauropus plicatus n. sp. Figs 12–20 Type locality. U.S.A., Tennessee, Blount Co., Great Smoky Mountains National Park, Reed Creek. Type specimens. Holotype: ad. 9 (Ƥ), 27 June 1997, leg. P.J. Obenauer. Paratypes: 1 ad. 9(3), 1 subad. 8(Ƥ), 1 juv. 5, Tennessee, Blount Co., Great Smoky Mountains National Park, Cades Cove, Parsons Branch Road, 5 minutes from Jet Force Creek Road, hemlock log litter, 35º 37.75N, 83º 51.62W, 28 July 2004, leg. S.A. Gil & J. Hilten; 1 ad. 9(Ƥ), North Carolina, Swain Co., Lakeshore Trail, Pilky Creek, UTM 0 2 57 998E, 39 25 761N, 14 April 2004, leg. A.J. Mayor. Nontypes: Tennessee, Blount Co., lower Gregory Ridge trail, 1 mile from trail-head, litter, Berlese extraction, 1 subad. 8(Ƥ), 28 July 2004, leg. A.K. Tishechkin & B. Blitz; Cooper Road Trail, 0.8 miles from trail-head, elev. 1211 ft, 35º 37.021N, 83º 55.608W, 1 subad. (Ƥ), 31 July 2004, leg. J. Ceigier & S.A. Gil. Sevier Co., Cades Cove, Crooked Arm Ridge Trail, 35º 36.659N, 83º 46.796W, conifer cones, Berlese extraction, 2 subad. 8(Ƥ), 31 July 2004, leg. B. Blitz & V.M. Bayless. – 9 specimens. Diagnosis . S. plicatus n. sp. belongs to a group of Nearctic species related by similarities in the general shape of the anal plate, subsimilar shape and length of the pygidial setae a 1, a 2 and a 3 and antennal globulus with a strikingly high number of bracts: S. californianus Remy, S. fratuelis Remy, S. canadensis Scheller and S. boreus Scheller. The first is widely distributed, known from NE Siberia (Scheller 1986), California (Remy 1958), British Columbia (Scheller 1984) and the southern Appalachians. The other three have, as far as we know now, restricted ranges. Thus S. boreus Scheller is known only from Alaska (Scheller 1986), S. fratuelis Remy only from Tennessee (Remy 1958) and S. canadensis Scheller only from British Columbia (Scheller 1984). The new species can be distinguished from these species particularly by the shape of the styli of the pygidial tergum (thin and pointed, not more or less thick and ...